18-Fluorodeoxyglucose Uptake by Positron Emission Tomography in Extraocular Muscles of Patients with and without Graves' Ophthalmology. (14th February 2013) - García-Rojas, Leonardo; Adame-Ocampo, Gloria; Alexánderson, Erick; Tovilla-Canales, José Luis
Abstract : Objective . To compare 18-fluorodeoxyglucose (FDG) uptake by positron emission tomography (PET) in extraocular muscles (EOMs) of patients with Graves' ophthalmopathy (GO) versus patients without GO. Design . Prospective, observational, comparative, and cross-sectional study. Participants . Thirty-two eyes of patients with GO and seventy eyes of patients without GO. Methods . We prospectively included patients older than 18 years of age with and without GO. FDG-PET imaging study was performed; standardized unit value (SUV max ) was quantified in EOMs. Standard deviation and significant statistical difference (P < 0.05 ) were calculated. Results . Thirty-two eyes of sixteen patients of the GO group were included, with a mean age of 44.31 (20–71) years. Seventy eyes of thirty-five patients of the group without GO were included, with a mean age of 49.20 (24–77) years. EOMs average uptake of the groups with and without GO were 3.38 ± 1.31 and 1.89 ± 0.51 SUV max (P < 0.05 ), respectively. Conclusion . FDG uptake was significantly increased in EOMs of patients with GO. PET gives valuable information and may be a helpful tool in detecting, localizing, and quantifying GO inflammation. Further research is needed to define the role of PET in detecting, grading, and following up GO in order to optimize treatment in the inflammatory stage.